Mummies in the Morning : Magic Tree House #3 - Osborne, Mary Pope, 1949- (New York : Random House, 1993)
Jack and his younger sister take a trip in their tree house back to ancient Egypt, where they help a queen's mummy continue her voyage to the Next Life.
"A First stepping stone book"
Booklist
Keywords: Mummies -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Time travel -- Fiction; Mummies -- Juvenile fiction; Time travel -- Juvenile fiction